The Influence Of Workload And Work Stress On Employee Performance At The Office Of Cooperatives, Small And Medium Enterprises Of Lampung Province - Linda Gusnila; Ariswandy, David (Utami Publisher, 2025)
Employee performance, particularly at the Office of Cooperatives, Small and Medium Enterprises of Lampung Province, is a crucial factor in achieving operational efficiency. However, high workload and stress often hinder target achievement, negatively impacting productivity, health, and employee motivation. Data indicating low target achievement suggest the need for improvements in workload management and stress management strategies. This study aims to analyze the influence of workload and stress on employee performance, contributing to human resource management in the public sector.This research is a quantitative field study designed to systematically and objectively describe facts and population characteristics. A random sample of 70 employees was selected, with a 10% margin of error, resulting in 41 respondents. The independent variables in this study are Workload (X1) and Work Stress (X2), which affect the dependent variable, namely Employee Performance (Y).Quantitative analysis shows that Workload (X1) affects employee performance (Y) by 12.0%, while Work Stress (X2) has a greater impact of 34.4%. Simultaneously, Workload (X1) and Work Stress (X2) together influence employee performance (Y) at the Office of Cooperatives, Small and Medium Enterprises of Lampung Province by 64,6%.